Combined anterior‐posterior approach with enlarged sciatic foramen to remove sciatic notch dumbbell‐shaped tumors. Issue 4 (30th January 2017) - Li, Mi; Li, Hao; Du, Yu; Cai, Zhuo; Liao, Hui; Guo, Fengjing; Chen, Anmin; Li, Feng; Yang, Caihong
Abstract : BACKGROUND AND OBJECTIVES: To explore a new method for resecting huge sciatic notch dumbbell‐shaped tumors. METHODS: Preoperative thin‐slide scanning magnetic resonance images (MRI) and computerized tomography angiography (CTA) scans were conducted. The images were processed to reconstruct a 3‐dimensional (3D) model. The relationship between the tumor and surrounding anatomical structures was accurately identified. By combining an anterior‐posterior approach, about 1.0 × 5.0 cm 2 c‐shaped bone around the greater sciatic foramen was removed using piezosurgery osteotomy to enlarge the sciatic notch, after which retroperitoneal dumbbell‐shaped tumors in the four patients were excised. RESULTS: Tumors in four patients were completely removed. Two patients obtain a total en bloc tumor resection; one patient was clinically determined to be a benign nerve‐sheath tumor which was removed within the sciatic nerve sheath, and one patient had an extremely asymmetric tumor shape. The tumor unexpectedly split at the dumbbell isthmus across the greater sciatic foramen during blunt dissection, while both sections were completely removed. CONCLUSIONS: The combined anterior‐posterior approach with an enlarged sciatic notch is an effective method to remove sciatic notch dumbbell‐shaped tumors. Compared to the reported study, it is a new method probably helpful for selected patients.